2013
DOI: 10.1111/jgh.12379
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 V617F mutation and 46/1 haplotype in Chinese Budd‐Chiari syndrome patients

Abstract: Our study showed that the presence of 46/1 haplotype increased the risk of JAK2V617F-positive BCS in China. In addition, low prevalence of JAK2V617F mutation in BCS patients suggested that myeloproliferative neoplasms (MPNs) should not be an etiological factor of BCS in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Previous studies have demonstrated that the distribution of thrombotic risk factors for Budd-Chiari syndrome was widely different between China and Western countries [14,[17][18][19]. This phenomenon could be extrapolated to nonmalignant and noncirrhotic patients with PVT because of the etiological similarity between PVT and Budd-Chiari syndrome.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have demonstrated that the distribution of thrombotic risk factors for Budd-Chiari syndrome was widely different between China and Western countries [14,[17][18][19]. This phenomenon could be extrapolated to nonmalignant and noncirrhotic patients with PVT because of the etiological similarity between PVT and Budd-Chiari syndrome.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, a particular somatic mutation (V617F) in the Janus tyrosine kinase-2 (JAK2) gene in myeloid cells was identified in a study of chronic MPD (14). This mutation has been detected in around 40% of patients with primary BCS (15)(16)(17). Other causes of BCS such as Behcet's disease (18,19), antiphospholipid syndrome (20), and oral contraceptives (21) have been reported.…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…Budd-Chiari syndrome (BCS) is a rare disorder consisting of hepatic venous outflow obstruction at any level of hepatic vein (HV) and/or inferior vena cava (IVC) resulting in portal hypertension [1][2][3]. Intervention treatment, including recanalization and transjugular intrahepatic portosystemic shunt (TIPS), has been widely used to treat BCS.…”
Section: Introductionmentioning
confidence: 99%